The Ethics of Price Variation - William A. Jackson (Forum for Social Economics, 2024)
Orthodox price theory turns on flexible prices that move frequently to maintain market-clearing equilibrium. Fixed prices are a source of market imperfections and failures. In the traditional ethics of pricing, by contrast, prices should be set at a just norm and stay there, with only rare amendments. The current paper examines these attitudes to price variation and finds them inadequate: orthodox economics is too supportive of continual price changes, while the traditional ethics dwell too much on the just price. A case is made for treating price stability as being distinct from the just price and valuable in itself. Rather than yearning for an elusive optimum, ethical assessment of pricing can then be based on acceptable ranges for the price level and price variation.
Keywords: D40; D63; L51; 330; ethics; pricing; stability; market power; regulation